Frankenstein Urbanism. Eco, Smart and Autonomous Cities, Artificial Intelligence and the End of the City. - Cugurullo, Federico (Routledge, 2021)
This book tells the story of visionary urban experiments, shedding light on the theories that preceded their development and on the monsters that followed and might be the end of our cities. The narrative is threefold and delves first into the eco-city, second the smart city and third the autonomous city intended as a place where existing smart technologies are evolving into artificial intelligences that are taking the management of the city out of the hands of humans. The book empirically explores Masdar City in Abu Dhabi and Hong Kong to provide a critical analysis of eco and smart city experiments and their sustainability, and it draws on numerous real-life examples to illustrate the rise of urban artificial intelligences across different geographical spaces and scales. Theoretically, the book traverses philosophy, urban studies and planning theory to explain the passage from eco and smart cities to the autonomous city, and to reflect on the meaning and purpose of cities in a time when human and non-biological intelligences are irreversibly colliding in the built environment. Iconoclastic and prophetic, Frankenstein Urbanism is both an examination of the evolution of urban experimentation through the lens of Mary Shelley’s Frankenstein, and a warning about an urbanism whose product resembles Frankenstein’s monster: a fragmented entity which escapes human control and human understanding. Academics, students and practitioners will find in this book the knowledge that is necessary to comprehend and engage with the many urban experiments that are now alive, ready to leave the laboratory and enter our cities.
Keywords: Stadtforschung; Stadtentwicklung; Stadtentwicklungsforschung; Urbanisierung; Nachhaltige Stadtentwicklung; Smart City; Künstliche Intelligenz; Gebaute Umwelt; Stadtökologie; Autonomie; Fallbeispiel